2014
DOI: 10.1007/s12648-014-0609-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of DC magnetic field on atmospheric pressure argon plasma jet

Abstract: In this work, external DC magnetic field effect on the atmospheric pressure plasma jet has been investigated, experimentally. The magnetic field has been produced using a Helmholtz coil configuration. It has been applied parallel and transverse to the jet flow. The strength of the DC magnetic field is 0-0.28 and 0-0.57 Tesla between the two coils in parallel and transverse applications, respectively. It has been shown that the plasma gas flow plays the main role in magneto-active collision-dominated plasma. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…on it [28][29][30]. Spectra shows that plasma composition for any arbitrary considered input powers are the same for two cases CAP and CAP+SMF but emission intensity increase in the presence of SMF, which is in agreement with previous result about RS and emission intensity of CAP in the presence of SMF [27,31]. 22 HO known as a main species in plasma treated medium that affect the biological system, and it is shown that production of 22 HO in plasma treated medium is not affected by SMF [27].…”
Section: Resultssupporting
confidence: 90%
“…on it [28][29][30]. Spectra shows that plasma composition for any arbitrary considered input powers are the same for two cases CAP and CAP+SMF but emission intensity increase in the presence of SMF, which is in agreement with previous result about RS and emission intensity of CAP in the presence of SMF [27,31]. 22 HO known as a main species in plasma treated medium that affect the biological system, and it is shown that production of 22 HO in plasma treated medium is not affected by SMF [27].…”
Section: Resultssupporting
confidence: 90%
“…It is, thus, highly interesting to understand what the effect will be at the plasma/ surface interface with a magnetic-assisted field under atmospheric-pressure conditions. Past studies applying magnetic field in the free-jet region of APPJ [23,24] have shown some interesting results. In this study, we would like to address this interesting yet important problem in a different way, where we focus on investigating the magnetic-field effect in the plasma/ substrate interface.…”
Section: Introductionmentioning
confidence: 98%
“…Some researchers [41][42][43] found that the introduction of the magnetic field enhances the discharge of plasma jets and the GA could also be pulled and stretched by the Lorentz force. Therefore, in this paper, we apply an external magnetic field to make the direction of Lorentz force on the discharge channel opposite to that of gas flow, so that the drag force of the air flow is offset and the motion of discharge channel is suppressed as much as possible.…”
Section: Introductionmentioning
confidence: 99%